Increasing Tourism and Halal Products in The Mandalika Circuit Area Through Sharia Homestay - Novi Yanti Sandra Dewi (Jurnal Ilmiah Ekonomi Islam, 2022)
Pertamina Mandalika Internasional Street Circuit in Lombok, West Nusa Tenggara, has become the attention of motorcycle racing lovers in various parts of the world today. This is because at the Mandalika Circuit the Idemitsu Asia Talent Cup, World Superbike, and MotoGP are held. However, the current number of 14,000 hotel rooms in West Nusa Tenggara is not sufficient for the number of World Superbike spectators of 25,000 people, MotoGP viewers of 160,000 people if the COVID-19 pandemic ends, and 114,000 people if the COVID-19 pandemic is still ongoing. . The number of viewers is not proportional to the number of hotel rooms available in West Nusa Tenggara. The number of hotels is far from sufficient, so that the lack of hotels to accommodate these tourists requires a solution. To find out the solution, an in-depth study with qualitative methods was carried out. One solution that is the result of this research is to empower the houses of the surrounding community to become halal homestays for tourists outside Lombok. Halal homestay is a sharia-based homestay that implements the sharia concept through product adjustments, services and management in accordance with sharia principles.